How a Service-Oriented Architecture May Change the Software Development Process. - HAINES, MARC N.; ROTHENBERGER, MARCUS A. (Communications of the ACM, 2010)
The article presents the results of research related to service-oriented computer network architectures, focusing on best practices for implementing organizational change, and the implications for software development. Structured interviews with information technology professionals who had dealt with such issues in the fields of insurance, financial services, state government, and entertainment were conducted. The research methodology is described, and an analysis of the results is presented. It was found that the adoption of more agile software development practices enabled organizations to make the best use of service-oriented architecture improvements.